GE_GERICHTE C/28956/2018 vom 18. Juni 2019 - GE Cour de justice (2019)
DROIT D'AUTEUR ET DROITS VOISINS ; SOCIÉTÉ DE GESTION ; COPIE ; TARIF(EN GÉNÉRAL) ; INTÉRÊT MORATOIRE | LDA.59.al1; LDA.59.al3; LDA.62.al2; CO.102.al1; CO.104.al1